Gastos em saúde e educaç\~ao no Brasil: Impactos da unificaç\~ao dos pisos constitucionais - Fabiola Sulpino Vieira; Luciana M. Santos Servo; Rodrigo Pucci de Sá e Benevides; Sérgio F. Piola; Rodrigo Octávio Orair (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– This text aims at investigating the effects of unifying the constitutional minimum levels for healthcare and education expenditures, especially in municipalities. It provides a contribution to the public debate on a series of legislative initiatives, such as the Constitutional Amendment Proposals 186/2019 and 188/2019. The analysis is based on primary data from budget reports of the Brazilian Union, the States and the Federal District, and the Municipalities. Results show that expenditures in both areas exceeded the sum of the minimums in each level of government. This surplus is higher for education, in the case of the Union, the States and the Federal District. Whereas in the case of Municipalities the surplus if higher for healthcare. The detailed analysis of expenditures (as percentage of total revenues) points that 80% of the 5,480 municipalities with available data were above 15.75% for healthcare and 26.25% for education, which exceeds the respective minimums of 15% and 25%. With regard to the risk of decreasing expenditures in a scenario of minimums unification, it is identified that 951 municipalities face a higher risk in the area of education, given the fact that their education expenditures are close to the border of the minimum and healthcare expenditures are above the minimum boundary. While 97 municipalities face higher risk in the area of healthcare, as the healthcare expenditure is close to the minimum border and education expenditure is far from it. These findings support the hypothesis that, in a context of competition between financial sources, healthcare expenditures tend to be more resilient, since they are less elastic, and, therefore, education expenditures are at greater risk of suffering losses.
Keywords: H51; H52; 330; healthcare financing; health expenditures; education expenditures; unified health system; Brazil